Rhizobial populations in soils from natural Acacia senegal and Acacia nilotica forests in Mauritania and the Senegal river valley - Sarr, A; Neyra, M.; Houeibib, MAO; Ndoye, I; Oihabi, A; Lesueur, Didier (Springer, 2005)
Eighty-two strains of rhizobia were isolated from soils taken from several sites in Mauritania and Senegal. These soil samples were collected from natural stands of Acacia nilotica and Acacia senegal. The soils from Mauritania were less rich in native rhizobia than the soils from Senegal. The strains were characterized using polymerase chain reaction restriction fragment length polymorphism and by sequencing the rDNA 16S 23S intergenic spacer region (IGS). They were sorted into seven IGS groups. These groups were not associated with the geographical origin of the strains or with the host-plant species at the site where the soils were collected. Most of the strains were in three of the IGS groups (I, IV, and V). One representative strain from each IGS group was sequenced and showed that the strains were from the genus Mesorhizobium. IGS groups I, IV, and VI were close to the species M. plurifarium (AF34563), IGS groups IIand III were close to the species Mesorhizobium sp. (AF510360), IGS group V was close to the species Mesorhizobium sp. (AF510366), and IGS group VII was close to Mesorhizobium sp. (AF510346).